Update on asthma and cleaning agents. Issue 2 (April 2017) - Folletti, Ilenia; Siracusa, Andrea; Paolocci, Giulia
Abstract : Purpose of review: Asthma due to cleaning products has been known for 20 years, and the interest in this topic is still large because of the number of cleaning workers with respiratory problems. In this review, we sought to highlight the most recent findings on the relationship between exposure to cleaning products and asthma and to summarize the specific literature published between 2013 and 2016. Recent findings: Women are confirmed as most of workers exposed to cleaning products and have a higher frequency than men of work-related respiratory symptoms and diseases. Many cases of asthma due to cleaning products occur in healthcare occupations. The increased risk of asthma has been shown to be related to the number of years in the job and to early life disadvantage. Recent evidence suggests that predisposition to adult-onset asthma may be related to interaction between genes and occupational exposure to low-molecular weight agents/irritants. There is some evidence that an irritant mechanism is more common, although several case reports showed animmunologic mechanism (e.g. disinfectants, amine compounds, aldehydes and fragrances). Summary: The review updated recent findings on epidemiology, cleaning agents and their mechanism, and prevention of asthma due to cleaning agents. This article provides new information on the level of exposure, which is still high in professional cleaners and even more in domestic cleaners, and on the frequency of asthma in professional and domestic cleaners. An irritant mechanism is more common, although an immunological mechanism is possible, especially in healthcare workers exposed to disinfectants.